TOP-10 questions about telemedicine counseling for cardiovascular patients. MONICA experience in 2020 - T. K. Chernyavskaya; K. E. Sobolev; A. V. Novikov; D. S. Zubkov (Кардиоваскулярная терапия и профилактика, 2021)
Changes in provision of elective care during coronavirus disease 2019 pandemic require search for new forms of doctor-patient communication. Telemedicine technologies have become widely used for monitoring of patients, especially those with noncommunicable diseases. However, the introduction of telemedicine care is associated with a large number of medical, legal and technical issues. Rational use of telecommunication within the modern clinical guidelines will significantly increase the availability of high-quality healthcare and reduce the hospitalization rate for exacerbation of chronic diseases, as well as improve disease outcomes.